L’Italia nello sguardo e nella poetica di V. E. Mejerchol’d - Attisani, Antonio (Mimesis Journal, 2019)
The article derives from a talk given at an important conference organised by Béatrice Picon-Vallin in Paris at the beginning of this century. It describes the relations between V. Meyerhold, Italy and Italian culture and highlights how they do mirror in his theatrical poetic. The director was in Italy three times. In 1902 he was very impressed by Milano, a «grotesque» setting inhabited by all the figures of an imminent revolution, but he sees and appreciates the old Tommaso Salvini. His second journey was in 1910, at the vigil of the Molière’s Don Juan transformed in a comédie-ballet, and the third in 1925, when in Rome he was on the Gogol’s footsteps, but also met the heretic Vjaceslav Ivanov and the unorthodox Maksim Gorki. The reader will notice how different from Stanislavsky’s is the Italian influence with respect to Meyerholdian poetic.